Motility and cytoskeletal organisation in the archigregarine Selenidium pygospionis (Apicomplexa): observations on native and experimentally affected parasites - Kováčiková, Magdaléna; Paskerova, Gita G; Diakin, Andrei; Simdyanov, Timur G; Vaškovicová, Naděžda; Valigurová, Andrea (Parasitology research, 2019)
Representatives of Apicomplexa perform various kinds of movements that are linked to the different stages of their life cycle. Ancestral apicomplexan lineages, including gregarines, represent organisms suitable for research into the evolution and diversification of motility within the group. The vermiform trophozoites and gamonts of the archigregarine Selenidium pygospionis perform a very active type of bending motility. Experimental assays and subsequent light, electron, and confocal microscopic analyses demonstrated the fundamental role of the cytoskeletal proteins actin and tubulin in S. pygospionis motility and allowed us to compare the mechanism of its movement to the gliding machinery (the so-called glideosome concept) described in apicomplexan zoites. Actin-modifying drugs caused a reduction in the movement speed (cytochalasin D) or stopped the motility of archigregarines completely (jasplakinolide). Microtubule-disrupting drugs (oryzalin and colchicine) had an even more noticeable effect on archigregarine motility. The fading and disappearance of microtubules were documented in ultrathin sections, along with the formation of α-tubulin clusters visible after the immunofluorescent labelling of drug-treated archigregarines. The obtained data indicate that subpellicular microtubules most likely constitute the main motor structure involved in S. pygospionis bending motility, while actin has rather a supportive function.
Keywords: Motility; cytoskelet; Protozoan Proteins; Cytoskeleton; Electron Microscope Tomography; aktiny; Apicomplexa; Tubulin; Microtubules; Parasites; tomografie elektronová; zvířata; Cytoskeletal drugs; trofozoiti; Ultrastructure; mikrotubuly; α-Tubulin; tubulin; paraziti; Actins; Animals; Actin; protozoální proteiny; Trophozoites